Criminal Liability of Notaries for Failure to Identify Beneficial Ownership in Banking Transactions - Anak Agung Linda Cantika; Ida Ayu Cintiya Kencana Dewi (NOTARIIL Jurnal Kenotariatan, 2026)
The increasing complexity of banking transactions and the growing misuse of legal entities for money laundering, terrorism financing, and other financial crimes have intensified the importance of identifying Beneficial Ownership within the banking sector. In Indonesia, notaries play a strategic role in the establishment of legal entities, authentication of legal documents, and facilitation of banking transactions. However, failures in identifying Beneficial Ownership may create legal consequences, particularly when such negligence contributes to unlawful financial activities. This study aims to analyze the criminal liability of notaries arising from the failure to identify Beneficial Ownership in banking transactions, as well as to examine the legal norms governing the obligations of notaries in implementing the principle of prudence and transparency. This research employs normative legal research using statutory, conceptual, and case approaches. The legal materials consist of primary legal materials including laws and regulations related to notarial duties, banking law, anti-money laundering law, and Beneficial Ownership regulations, as well as secondary legal materials derived from legal doctrines and scholarly literature. The results indicate that notaries may bear criminal liability when their failure to identify Beneficial Ownership fulfills the elements of criminal negligence or intentional participation in unlawful financial transactions. Furthermore, the existing legal framework regarding Beneficial Ownership obligations for notaries remains fragmented and lacks harmonization, leading to legal uncertainty in practice. Therefore, stronger regulatory frameworks and clearer legal standards are necessary to enhance legal certainty, accountability, and preventive measures against financial crimes in banking transactions.